(untitled) (Clinics, 2011)
BACKGROUND AND AIM: Biliary fistulas are the most common morbidity (8.2-26%) following hydatid liver surgery. The aim of our study was to reduce the incidence of postoperative biliary fistulas after the suturing of cystobiliary communications by applying a bile leakage test. PATIENTS AND METHODS: A total of 133 hydatid liver cysts from 93 patients were divided into two groups, according to whether the test was performed. Tests were performed on 56 cysts from 34 patients, and the remaining 77 cysts from 59 patients were treated without the test. In both groups, all visible biliary orifices in the cysts were suture ligated, and drains were placed in all cysts. The visibility of the biliary orifices and postoperative biliary drainage through the drains were recorded. Patients in both groups were also compared with respect to the number of days living with the drains, the length of the hospital stay, and secondary interventions related to biliary complications. RESULTS: Biliary orifices were more visible in the tested cysts (13% vs. 48%; P